2023
DOI: 10.3389/fnmol.2023.1313635
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing traumatic stress-induced structural plasticity in a medial amygdala pathway using mGRASP

Caitlyn J. Bartsch,
Jessica T. Jacobs,
Nooshin Mojahed
et al.

Abstract: Traumatic stress has been shown to contribute to persistent behavioral changes, yet the underlying neural pathways are not fully explored. Structural plasticity, a form of long-lasting neural adaptability, offers a plausible mechanism. To scrutinize this, we used the mGRASP imaging technique to visualize synaptic modifications in a pathway formed between neurons of the posterior ventral segment of the medial amygdala and ventrolateral segment of the ventromedial hypothalamus (MeApv-VmHvl), areas we previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 64 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…We began by assessing the impact of SD during adolescence on long-lasting aggression in C57 mice. We previously showed that traumatic stress during adolescence in the form of non-contingent foot shock could promote long-lasting aggression ( Nordman J. et al, 2020 ; Nordman J. C. et al, 2020 ; Bartsch et al, 2023a , b ). However, given the comorbidity of childhood physical abuse and violent aggression later in life ( Widom, 1989 ; Caspi et al, 2002 ; Widom and Brzustowicz, 2006 ), and to simulate a more ethologically realistic stressful encounter to humans, for this study we elected to use SD as our traumatic stressor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We began by assessing the impact of SD during adolescence on long-lasting aggression in C57 mice. We previously showed that traumatic stress during adolescence in the form of non-contingent foot shock could promote long-lasting aggression ( Nordman J. et al, 2020 ; Nordman J. C. et al, 2020 ; Bartsch et al, 2023a , b ). However, given the comorbidity of childhood physical abuse and violent aggression later in life ( Widom, 1989 ; Caspi et al, 2002 ; Widom and Brzustowicz, 2006 ), and to simulate a more ethologically realistic stressful encounter to humans, for this study we elected to use SD as our traumatic stressor.…”
Section: Resultsmentioning
confidence: 99%
“…We chose foot shock as it is a more reliable stressor than SD due to the variability of CD1 attacks and because we have consistently shown that foot shock activates MeApv neurons in vivo . We began by administering intraperitoneal (IP) injections of 1 mg/kg CNO, the effective dose in our previous study ( Bartsch et al, 2023b ), or vehicle 30 min before non-contingent foot shock ( Figures 4A , B ). The mice were then euthanized 30 min later for c-Fos immunolabeling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations